Bagaimana Emosi Senang dan Bosan Tampak Dalam Pembelajaran Matematika Siswa SMP? - Firdausa Yanuar; Pradnyo Wijayanti (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Students' daily lives at school are characterized by a range of emotions. In recent years there has been interest in these emerging emotions, as they have been shown to affect future performance and learning. One sub-group of these emotions is the emotion of achievement. However, there is very little research on how achievement emotions emerge during mathematics learning. This study was conducted to find out how the achievement emotions of enjoyment and boredom emerge when learning mathematics in grade 7 junior high school students. A total of 31 students from class VII-A SMPN 1 Buduran participated in this study. The research type is  descriptive quantitative and was conducted by giving a questionnaire of achievement emotions to these 31 students and conducting interviews with 10 students. The research result shows that these two emotions can exist in one math learning meeting due to certain things such as how the teacher manages the class in learning and both occur in different phases of learning. Keywords: Achievement emotion, enjoyment, boredom, mathematics learning